‘FLATTENING’ THE PANDEMIC CURVE: HOW PRACTICING INFORMATION HYGIENE COULD HELP - Lazuardyas Zhafran Ligardi (OISAA, 2022)
This study presents an insight of the condition of infodemic in Indonesia and to provide solutions by practicing information hygiene could help in mitigating coronavirus disease (COVID-19) infodemic. Public health agencies and the WHO acknowledge infodemiology as an important new research discipline and vital area of practice during a pandemic. The purpose of this study is to provide insights into how the practice of information hygiene could also tackle the COVID-19 pandemic from the point of view of information science. In order to undertake this research, content analysis method is used with qualitative approach. This study concludes that practicing information hygiene by sanitizing before sharing is needed to overcome misinformation and disinformation.